Direção de atores no cinema: estudo de caso a partir de No Coração do Mundo (2019) - Leandro Monteiro Oliveira Pinho (2021)
Wandering through the historical journeys of Brazilian Cinema, one can understand how, in the last years, news agents emerged in the cinematic scene. Amongst them, Filmes de Plástico, a well renowned production company with more than 50 awards on their resume. Their last film, In the Heart of the World (2019) by Maurílio Martins and Gabriel Martins, is responsible for putting together important themes of Brazilian cinematography, present since Cinema Novo and Marginal Cinema until the Newest Brazilian Cinema Wave, affirming its own place. One of its main and most rich characteristics is the composition of its cast and the way the directors reach organic acting and lively and complex characters working with actors whose professional experiences and qualifications are very different. In the Heart of the World is a rich cinematographically experience, able to update paradigms of the studies and practices related to actor directing for films. Their actors’ multiplicities and directors’ technical abilities to equalize the actors in the same tone to create a work filled with unity is the impulse of the present research. It used especially the principles of Ismail Xavier, Paulo Emílio Sales Gomes, Jean-Claude Bernadet, Lia Bahia and Maria Carolina Vasconcelos Oliveira to talk about Brazilian Cinema history and the circumstances that have facilitated the emergence of Filmes de Plástico as a cultural agent. Walmeri Kellen Ribeiro, Constantin Stanislavski e Vsevolod Pudovkin are used to theorize about film acting and bound its course throughout global and Brazilian cinema history. Jacques Aumont and other authors are used to study film staging, dramatization and dedramatization to localize In the Heart of the World’s hybrid place. The data concerning the acting directing process of the film is used to illustrate, reinforce, or challenge principles about cinematographic actors acting.